(untitled) (Heritage, 2026)
The health system in Serbia was underdeveloped, which was also contributed to by the destruction of the health infrastructure and the loss of educated personnel during First World War. This is a territory whose cultural and educational level was far below that of the northwestern regions of Yugoslavia, due to a lack of funds and professional personnel. In addition to treatment, one of the measures was the education of the population, in which, in addition to the Ministry of Social Policy and Public Health, the Ministry of Physical Education was also involved. The goal was to influence, through lectures, a change in hygiene habits, especially among children. In addition to doctors and nurses, teachers were also involved in this action. In terms of the number of lectures held, the Morava banovina lagged behind other parts of the country, which can be explained by a lack of funds, but also by the lack of interest of the listeners. The attention paid to health institutions is best seen based on budget items, with the Department of Social Policy and Public Health coming in second place in terms of expenditure, right behind the Technical Department.